Adipokine Physiology and its Role in Female Obesity-Related Infertility - Zina Lafta Hassan; Azhar. A. Ameen; Suhyila Fadhil Ali; Osama A. mohsein (American Journal of Biology and Natural Sciences, 2025)
Background; Adipokines are bioactive molecules secreted by adipose tissue that play a critical role in regulating metabolic and reproductive functions. In obese females, dysregulated adipokine levels can impair ovarian function, disrupt hormonal balance, and contribute to infertility. Aims of the study; To investigate the physiological roles of adipokines and evaluate their impact on hormonal regulation and reproductive function in obese females with infertility. Methodology; This case-control study (Jan–May 2024) investigated adipokines in female obesity-related infertility. It included 150 obese infertile women and 50 healthy controls (aged 20–40) from fertility clinics in Nasiriyah, Iraq. Exclusion criteria ruled out PCOS, thyroid disorders, diabetes, and recent hormonal therapy. Blood samples were collected, processed, and stored at –20°C. Serum adipokines (leptin, adiponectin, resistin, visfatin) were measured by ELISA. Reproductive hormones (FSH, LH, estradiol, progesterone) were analyzed using the Cobas e411 analyzer (Roche Diagnostics, Germany). Result; The study showed significant differences in BMI, marriage duration, education level, adipokine levels, and reproductive hormones between obese infertile women and healthy controls. Leptin, resistin, and visfatin were elevated, while adiponectin, estradiol, and progesterone were reduced in patients. Strong correlations were found between adipokines, BMI, and reproductive hormones, suggesting that altered adipokine profiles in obesity negatively affect the hypothalamic-pituitary-ovarian axis, contributing to hormonal imbalance, ovulatory dysfunction, and infertility in women. Conclusions; Adipokines significantly impact female obesity-related infertility by altering reproductive hormone levels. Elevated leptin, resistin, and visfatin, alongside reduced adiponectin, disrupt the hypothalamic-pituitary-ovarian axis, impairing ovulation. These imbalances reflect adipose tissue’s role as an endocrine disruptor.